First records of Elachistinae from New Caledonia: evidence of repeated dispersal events with Australia (Lepidoptera, Gelechioidea, Elachistidae) - Kaila, Lauri (Zootaxa, 2017)
The first records of Elachistinae (Lepidoptera, Elachistidae) are reported from New Caledonia. Eight species are recognized. Elachista cynopa Meyrick is reported outside Australia for the first time. All other species are described as new: Elachista concubia sp. nov., E. achlyodes sp. nov., E. scoteina sp. nov., E. cardiaca sp. nov., E. dilobates sp. nov., E. vespertina sp. nov. and E. fugax sp. nov. All the new species have sister-species level relatives in Australia. E. fugax is attributed to Elachista sg. Elachista. All other species are placed in Elachista sg. Atachia. Following Kaila’s (2011) system E. achlyodes and E. concubia belong to the E. catarata section of the E. gerasmia group; E. cardiaca, E. dilobates, E. scoteina and E. vespertina belong to the E. gerasmia section of E. gerasmia group. Further, E. cardiaca is a member of the E. paragauda species complex, E. scoteina a member of the E. gerasmia species complex, and E. dilobates, E. vespertina of the E. cynopa species complex; E. dilobates is morphologically close to E. toryna Kaila. This pattern suggests at least six separate dispersal events between Australia and New Caledonia.